The relation between preschool children’s language development and their mothers’ depression and anxiety symptoms: a cross-sectional study - Göker, Zeynep; Eser, Havva; Yılmaz, Arzu (The European Research Journal, 2020)
Objectives: In this study, the relationship between preschool age group children’s language development and depression/anxiety symptoms of their mothers was investigated. Methods: Children aged 13-75 months and their mothers were included. Denver-II test and Beck Depression and anxiety scales were utilized. SPSS 17.0 program was used and p < 0.05 was considered as significant. Results: Of the 58 patients, 74.1% were male, with the mean age of 53.3 months. The mean maternal age was 31.5 years. The mean education level was 8.3 years for mothers. According to the Denver-II of language development, 53.4% of the cases were found to be "delayed" whereas 46.6% of all were “normal”, with significantly lower in “delayed” children (47.4 vs. 60 months; t (56) = -3.431, p = 0.001). Delayed language was significantly associated with lower mothers’ education level (7.4 vs. 9.3 years; t (56) = -2.466, p = 0.017). The median score of depression scale was significantly higher in the delayed language (18 vs. 13; z = -2.218, p = 0.027). Positive correlation was found between the mothers’ education and the language development (r = .324, p = 0.013). The anxiety symptom levels of the mothers were not associated with language development (p > 0.05). Conclusions: The level of education of mother seems to affect language development. There is a relationship between the depressive symptoms of the mother and the delay in language development. It seems important that the mothers of the cases whose children had language development to be directed to psychiatric evaluation.